Chemical characterisation of selected food processing wastewater - Tan, Jason Pei Sheng (Nanyang Technological University, 2021)
The food processing industries is a broad and varied field, consisting of a variety of industries which include dairy, beverage, and distillery. Wastewater from these industries has significant potential for resource recovery due to the high concentrations of degradable organics and nutrients, with the added benefits of the absence of pathogens, toxic heavy metals, and other hazardous contaminants. The recovery of the elements; Carbon, Nitrogen, and Phosphorus from the wastewater is the main scope of the project as they form the essential macronutrient needed for nutrient recovery. The chemical characteristics of wastewater play a major role in selecting the type of treatment and possible resource recovery method to be carried out. Analyses of broad characteristics are often crude: chemical oxygen demand (COD), biological oxygen demand (BOD), suspended solids (SS), total organic carbon (TOC), and total nitrogen (TN). However, the chemical composition of these wastewaters remains relatively undefined as there has been little attempt to analyse specific components in these wastewaters due to the complexity of analysing the various substrates and microbial products present in the wastewater. For this project, advanced instruments such as gas chromatography-mass spectrometers were used to analyse wastewater samples obtained from beverage processing plants, Asia Pacific Breweries (APB) and Mr Bean. These samples will then be used to promote the growth of biomass in the bioreactor. The test was conducted with four bioreactors with different sludge bedding to examine the effects of different microbe on the production of the types of intracellular components such as glycogen and Polyhydroxyalkanoates (PHA). The parameters crucial to the production of the carbon products such as amino acid and volatile fatty acid were analysed to determine the correlation between the acids and the production rate of intracellular components in each bioreactor. The study was able to successfully identify the various parameters in both the influent and effluent wastewater and the intracellular components produced in the biomass of all four bioreactors after the biotransformation process. The study concludes that there is a correlation between the type of amino acid produced and the rate of volatile fatty acid consumption in the production of the type and concentration of PHA. However, this analysis is rudimentary, and more tests would be needed to identify the types of microorganisms involve in the biotransformation process to have a more accurate analysis.